PREPARATION AND CHARACTERIZATION OF ITRACONAZOLE TRANSDERMAL PATCHES CONTAINING SINGLE-PHASE EMULGEL - ELHASSAN, GAMAL OSMAN (International Journal of Applied Pharmaceutics, 2022)
Objective: Emulgel technique has attempts for preparation of itraconazole (ITZ) transdermal patches of reservoir type using a single-phase system with different polymers of Carbopol 934 and Carboxy methyl cellulose (CMC). Methods: The transdermal patches were prepared by using eudragit L30 as a polymer and propylene glycol (PG) as plasticizer has been made to predict the mechanism of drug release and absorption based on the order of release. The optimized transdermal patches were characterised as surface morphology, pH, viscosity, spreadability, folding endurance, drug permeation, assay, in vitro dissolution and stability for 3 mo. Results: The result of the study showed that the transdermal patches prepared with eudragit (8 %) showed 96.11±3.17 % drug release in 24 h and the optimised formulation F8, which had the highest concentration of span 20 and tween 20, displayed the highest percentage of drug penetration. The drug release kinetics was studied, including the Baker-Lonsdale model with in vitro drug permeation data was found that release from non-spherical matrices, the first-order model with non-fickian diffusion. Conclusion: ITZ administered transdermally might be avoided the number of drawbacks associated with oral delivery and perhaps maintain a relatively constant plasma level during a lengthy course of treatment.